Effect of accelerated ageing on viability and longevity of wheat (Triticum aestivum) seed - PATIL, KALYANIRAO G; KARJULE, AVINASH; PATEL, D A; SASIDHARAN, N (The Indian Journal of Agricultural Sciences, 2019)
The accelerated ageing test (AAT) has been successfully used to rank and determine germinability of seed lots in various kind and varieties. An experiment was conducted to determine the influence of artificial ageing on seed viability and longevity of wheat seed of 2 varieties, viz. GW 496 and Lok 1. Progressive ageing period resulted in lowered seed quality in both wheat varieties. Combined effect of varieties and ageing duration showed the significant effect on all the observed seed quality parameters and recorded significant variation in these characters during (2015-16 and 2016-17) and in pooled analysis. The fresh seeds (without ageing) of wheat variety Lok 1 recorded highest average pooled germination (97. 50%), seedling vigour index I (2166), seedling vigour index II (20. 32) as well as observed biochemical parameters at the end of 5 days of accelerated ageing. Progressive ageing duration showed negative effect on biochemical parameters of the 5 days aged seeds of wheat variety GW 496 recorded lowest average pooled protein content (9.78%), carbohydrate content (60.36%), Î± amylase assay (6.19 micromoles/mg/min) and higher electrical conductivity (28.60 Î¼S/cm/g) due to fast deterioration at the end of artificial ageing.